2015
DOI: 10.1590/s0100-736x2015000500009
|View full text |Cite
|
Sign up to set email alerts
|

Equine proliferative enteropathy on a Brazilian farm

Abstract: ABSTRACT. - Lawsonia intracellularis infection on a horse farm in the Midwest region of Brazil is described. Thirty-nine foals a few days to months old from a herd with 300 horses, experienced diarrhea with variable characteristics and intensities, weight loss, hyperemic mucous membranes and dehydration. In foals 3 to 6 months of age, hypoproteinemia associated with submandibular edema were also common. Intestinal fragments of a 7-month-old foal were sent to an animal disease laboratory for diagnosis. The obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Moreover, animals with positive fecal qPCR may be in the early stage of infection and have been sampled before seroconverting (Pusterla & Gebhart, 2013). Gabardo et al (2015) described similar results, in which none of the three animals that were positive in serological testing showed positivity by the PCR technique. Vannucci, Pusterla, Mapes and Gebhart (2012) observed that foals inoculated with horse isolates eliminate L. intracellularis 12 to 38 days after infection and that serological detection occurrs only from 14 days after contact with the bacterium.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…Moreover, animals with positive fecal qPCR may be in the early stage of infection and have been sampled before seroconverting (Pusterla & Gebhart, 2013). Gabardo et al (2015) described similar results, in which none of the three animals that were positive in serological testing showed positivity by the PCR technique. Vannucci, Pusterla, Mapes and Gebhart (2012) observed that foals inoculated with horse isolates eliminate L. intracellularis 12 to 38 days after infection and that serological detection occurrs only from 14 days after contact with the bacterium.…”
Section: Resultsmentioning
confidence: 71%
“…Unlike most infections in swine, the proliferative lesion in horses can occur in the duodenum and in segments of the large intestine (Gabardo, Sato, Resende, & Guedes, 2015). Foals at weaning age are the most affected and may develop lethargy, anorexia, weight loss, colic, diarrhea and hyperthermia and death (Gabardo et al, 2015;Bohlin, Olsen, Laursen, Ohman, & Van Galen, 2019). However, adult animals can also occasionally develop a similar condition (Pusterla & Gebhart, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease has been described as emerging in the North American horse population [20], with larger outbreaks described in the United States [8] and Canada [4]. Additionally, single cases have been reported from Switzerland [21], England [22], Belgium [23], Israel [24], Brazil [25] and Australia [26]. In Denmark, a previous seroprevalence study showed that 5% of young horses admitted to a Danish referral hospital (University of Copenhagen Large Animal Teaching Hospital) had measurable L. intracellularis serum antibodies [27].…”
Section: Introductionmentioning
confidence: 99%